2018
DOI: 10.1145/3302261.3236703
|View full text |Cite
|
Sign up to set email alerts
|

Using Flipgrid to Increase Students' Connectedness in an Online Class

Abstract: Flipgrid, a free video discussion forum tool, increases students' perceptions of connectedness in the online classroom. Video discussion forums embedded in an online course can be used in many ways to connect instructors to students, and students to their peers. Embedding a tool that brings voice, tone, and body language to the online classroom strengthens connectedness and can increase civility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
2
15
0
5
Order By: Relevance
“…Speaking time, collaboration, student confidence, and pronunciation are all language skills Flipgrid use could potentially benefit. Additionally, Bartlett (2018) found that Flipgrid use increases students' perceptions of connectedness in the online classroom. As such, this research team proposes the following hypothesis:…”
Section: Online Community Engagement Tool: Flipgridmentioning
confidence: 96%
See 1 more Smart Citation
“…Speaking time, collaboration, student confidence, and pronunciation are all language skills Flipgrid use could potentially benefit. Additionally, Bartlett (2018) found that Flipgrid use increases students' perceptions of connectedness in the online classroom. As such, this research team proposes the following hypothesis:…”
Section: Online Community Engagement Tool: Flipgridmentioning
confidence: 96%
“…Flipgrid has been gaining momentum throughout the Pedagogy literature (Bartlett, 2018;Miskam & Aminabibi, 2019;Saçak & Kavun, 2020). The use of Flipgrid has been found to increase online student engagement and community (Johnson & Skarphol, 2018).…”
Section: Online Community Engagement Tool: Flipgridmentioning
confidence: 99%
“…It has been used to increase engagement in primary and secondary education, as well as online undergraduate courses. 5 The use of Flipgrid in doctoral education is limited, but has been described in online Masters-level nursing programs. 6 While many levels of learners have utilized Flipgrid as an online discussion platform, literature on the use of Flipgrid as a self-reflection tool has not been published.…”
Section: The Innovationmentioning
confidence: 99%
“…La segunda consecuencia fue que las clases presenciales se transformaron en clases en remoto. En la enseñanza a distancia los/las estudiantes pueden sentirse solos (Bartlett, 2018;Holbeck & Hartman, 2018). Sin duda, esta sensación pudo verse reforzada por las medidas de restricción de la movilidad implementadas para frenar la propagación del virus.…”
Section: Introductionunclassified
“…Sin duda, esta sensación pudo verse reforzada por las medidas de restricción de la movilidad implementadas para frenar la propagación del virus. Varios Pros y contras de Flipgrid en la clase de lenguas extranjeras Editorial Universitat Politècnica de València autores consideran que Flipgrid puede ser beneficioso en el aprendizaje en línea porque incrementa la presencia social de los/as estudiantes (Bartlett, 2018;Saçak & Kavun, 2019) y humaniza el entorno de aprendizaje (Craig, 2019). Flipgrid (https://info.flipgrid.com/) es una plataforma de comunicación asíncrona multimodal disponible de forma gratuita en los principales sistemas operativos (Windows, Android, Mac, etc.).…”
Section: Introductionunclassified